Dietitians Australia position statement on telehealth. Issue 4 (28th June 2020) - Kelly, Jaimon T.; Allman‐Farinelli, Margaret; Chen, Juliana; Partridge, Stephanie R.; Collins, Clare; Rollo, Megan; Haslam, Rebecca; Diversi, Tara; Campbell, Katrina L.
Abstract: It is the position of Dietitians Australia that clients can receive high‐quality and effective dietetic services such as Medical Nutrition Therapy (MNT) delivered via telehealth. Outcomes of telehealth‐delivered dietetic consultations are comparable to those delivered in‐person, without requiring higher levels of additional training nor compromising quality of service provision. Dietitians Australia recommends that policy makers and healthcare funders broaden the recognition for telehealth‐delivered dietetic consultations as a responsive and cost‐effective alternative or complement to traditional in‐person delivery of dietetic services. The successful implementation of telehealth can help to address health and service inequalities, improve access to effective nutrition services, and support people with chronic disease to optimise their diet‐related health and well‐being, regardless of their location, income or literacy level, thereby addressing current inequities.